POVERTY AS A CRITICAL CONSTRAINT TO SUSTAINABLE DEVELOPMENT IN UKRAINE - Mykhailo Kotenok; Volodymyr Kyrylenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article is devoted to the study of the relationship between the size and structure of consumer expenditures of Ukrainian households (as characteristics that largely depend on the economic effectiveness and state income policy) and the potential for intensifying household participation in financing the development of the social sphere (as a prerequisite for Ukraine's approach to the trajectory of sustainable economic development). The theoretical background of the study is formed by the works of C. Boulding, W. Nordhaus and H. Hotelling and scholars united by the research paradigm of the Club of Rome. According to the methodology of sustainable development theories, the authors interpret the spread and deepening of poverty not only as a direct manifestation (result) of negative trends in socioeconomic life but also as a limitation of opportunities for socio-economic development in Ukraine. Accordingly, the characteristics of the concentration of consumer expenditures of Ukrainian households are used as the main criterion for assessing their potential to participate in shaping the preconditions for overcoming negative trends in economic efficiency and living standards of the general population. To assess the degree of concentration of consumer expenditures in Ukrainian households, the Herfindahl-Hirschman indices and the Entropy indices are calculated. The size of the entropy indicator of consumer expenditures of Ukrainian households indicates the inconsistency of their economic behaviour with models of inclusive and sustainable development, and the sustainability over the retrospective period indicates the lack of positive trends in activating the role of consumer expenditures in increasing investment in human capital, which makes it impossible for the social sphere to be sustainable in the context of political unrest, a global pandemic and military conflicts and the militarization of the economy.